Solving the n-player Tullock contest - Christian Ewerhart (University of Zurich, Department of Economics, 2024)
The n-player Tullock contest with complete information is known to admit explicit solutions in special cases, such as (i) homogeneous valuations, (ii) constant returns, and (iii) two contestants. But can that model be solved more generally? In this paper, we show that key characteristics of the equilibrium, such as individual efforts, winning probabilities, and payoffs cannot, in general, be expressed in terms of the primitives of the model using basic arithmetic operations plus the extraction of roots alone. In this sense, the Tullock contest is intractable. We argue that our formal concept of tractability captures the intuitive understanding of the notion.
Keywords: C02; C72; D72; 330; Tullock contest; Pure-strategy Nash equilibrium; Solution by radicals; Galois theory